Sleep Impairment in Attention Deficit Hyperactivity Disorder (ADHD): Is it an Additional Symptom of the Disorder, Due to ADHD Comorbidities or a Common Sleep Disorder of Childhood and Adolescence Aggravated by the Disorder? - N. Gadoth (Medical Research and Its Applications Vol. 8, 2024)
This chapter is dedicated to sleep impairment in attention deficit hyperactivity disorder. Attention Deficit Hyperactivity Disorder (ADHD) is a quite common neuropsychiatric ailment affecting all ages. Sleep impairment is associated with widespread regional changes in brain activity involved in sustained attention, distraction, impulsivity and memory, as shown by numerous objective methods. Sleep problems which are very common in children and adolescents without ADHD present as either insufficient or impaired sleep. The diagnosis of ADHD lacks a biological marker and is based only on clinical judgment. Therefore, overdiagnosis and underdiagnosis are not uncommon. Since it is a developmental disorder, the clinical characteristics vary with age, nevertheless. the majority of affected individuals exhibit the traditional "triad" of impulsivity, hyperactivity, and inattention. A number of comorbidities are associated with the disorder and in many patients, their presence imposes a negative effect on life quality which may be more prominent than that caused directly by the classical "triad". Although cases with the triad have been reported during the last 200 years, the concept of ADHD was solidified in 1987. It has taken some time for sleep disturbance to be identified as a significant comorbidity of ADHD. It is surprising that the DSM-5 did not mention sleep impairment in relation to ADHD. This study reviews the traits, prevalence, and potential cause of sleep disturbance in children and adults with ADHD. Also, the bidirectional association between impaired sleep quality and ADHD is discussed in an attempt to clarify whether impaired sleep is an additional symptom of “pure” ADHD, is the sole result of associated comorbidities, or is the result of both.